EFFECTS OF MINIMALLY INVASIVE PLATE OSTEOSYNTHESIS (MIPO) ON PATIENTS WITH DISTAL TIBIA FRACTURES: A CROSS-SECTIONAL STUDY. - Chand, Subhash; Kumar, Naveen (Student's Journal of Health Research Africa, 2024)
Background Distal tibia fracture accounts for around 6-11% of tibia fractures. A distal tibia fracture is also known as a Pilon fracture. A distal tibia fracture is not easy to handle. The prime motive of this research is to examine the result of minimally invasive plate osteosynthesis for distal tibia fractures. Materials and Methods A cross-sectional study was conducted, and 107 patients were included in this research. All the detailed history of the patients was recorded. Complete lesion detersion was first done. Advance soft tissue covering is performed if needed. Plates are arranged on the lateral side of the tibia. If it is required, extra cortical screw utilizing minimally invasive plate osteosynthesis. Results The study examined the effects of Minimally Invasive Plate Osteosynthesis (MIPO) on distal tibia fracture patients found 70 males, 37 females, with most aged 30-40 years (45), then 40-50 years (40), 20-30 years (13), and 50-60 years (9). Professions varied: farmers (50), businessmen (35), daily wage workers (11), office workers (11). Road accidents caused 65 injuries, falls 42. Injuries were split between right (52) and left sides (55). These insights deepen understanding of MIPO's impact on distal tibia fracture patients. Conclusion The study indicates that minimally invasive plate osteosynthesis (MIPO) has minimal impact on blood circulation, promoting faster recovery with less hematoma and trauma. MIPO also accelerates bone union, requiring minimal time and no specialized instruments. Non-union reasons include pressure, fragment issues, and fracture design. Recommendation Minimally invasive plate osteosynthesis is a safe, effective treatment for distal tibia fractures, yielding quick bone union, improved leg mobility, and ample blood supply to the periosteum. It's a favorable option for treating such fractures.